Examination and characterisation of burst spinal cord stimulation on cerebrospinal fluid cellular and protein constituents in patient responders with chronic neuropathic pain - A Pilot Study - Conroy, Melissa (My University, 2020)
Introduction: Patients with neuropathic pain have altered proteomic and neuropeptide constituents in cerebrospinal fluid (CSF) compared to controls. Tonic spinal cord stimulation (SCS) has demonstrated differential expression of neuropeptides in CSF before and after treatment suggesting potential mechanisms of action. Burst-SCS is an evidence-based paraesthesia free waveform utilised for neuropathic pain with a potentially different mechanistic action to tonic SCS. This study examines the dynamic biological changes of CSF at a cellular and proteome level after Burst-SCS. Methods: Patients with neuropathic pain selected for SCS had CSF sampled prior to implant of SCS and following 8 weeks of continuous Burst-SCS. Baseline and 8-week pain scores with demographics were recorded. T cell frequencies were analysed by flow cytometry, proteome analysis was performed using mass spectrometry and secreted cytokines, chemokines and neurotrophins were measured by enzyme-linked immunosorbent assay (ELISA). Results: 4 patients (2 females, 2 males) with a mean age of 51 years (+/-SEM 2.74, SD 5.48) achieved a reduction in pain of >50% following 8 weeks of Burst-SCS. Analysis of the CSF proteome indicated a significant alteration in protein expression most related to synapse assembly and immune regulators. There was significantly lower expression of the proteins: growth hormone A1 (PRL), somatostatin (SST), nucleobindin-2 (NUCB2), Calbindin (CALB1), acyl-CoA binding protein (DBI), proSAAS (PCSK1N), endothelin-3 (END3) and cholecystokinin (CCK) after Burst-SCS. The concentrations of secreted chemokines and cytokines and the frequencies of T cells were not significantly changed following Burst-SCS. Conclusion: This study characterised the alteration in the CSF proteome in response to burst SCS in vivo. Functional analysis indicated that the alterations in the CSF proteome is predominately linked to synapse assembly and immune effectors. Individual protein analysis also suggests potential supraspinal mechanisms.
PUBLISHED
Keywords: Neural interface; Neuroimmune; Neuropathic pain; Spinal cord stimulation; Immunology, Inflammation & Infection; Neuroscience; Biomedical sciences; Chronic inflamation; Clinical research, trials; Medicine; Chronic Health Condition; Health